Análise da construção da política pública municipal de educação ambiental no município de Conceição da Barra - ES - Brandao, Paola Larissa (2019)
We sought to analyze the process of implementation of the Conceição da Barra Municipal Environmental Education Policy (PMEA), investigating the perception of school managers and teachers regarding the provision of environmental education in the municipality, analyzing the actions of formation and popular participation in the process. construction of Public Policy and evaluating the methodology adopted. Through a research characterized as qualitative and, through its technical procedures, as action research, data were collected through documentary research, questionnaire application and observations of the formation, mobilization and popular participation in the construction processes. of public policy. The field research was conducted from November 2017 to December 2018. The results show that more than half of the teachers and school managers participating in the research have no training in environmental education. In addition, it was found that a naturalistic / pragmatic perception about the environment and the field of environmental education prevails among them, disregarding the social aspects. Regarding the effectiveness of the provision of environmental education, there was divergence between the answers, as 50% of teachers and 76.47% of managers responded that this right is guaranteed through cross-cutting activities in the disciplines and projects. The analysis of the methodology used in the process of construction of the PMEA showed that it was based on the concept of critical environmental education, based on emancipatory, transformative, democratic, participatory and dialogical principles, which culminated in a bill representing territories with potential to contribute to the change of social and environmental reality in the municipality.